Temporary waqf vis-à-vis hibah umra and ruqba - Rahman, Habibur; Osmani, Noor Mohammad (UiTM Press, Universiti Teknologi MARA, 2018)
Waqf is one of the ways prescribed in Islam to disseminate the wealth among more people as much as possible. If wealth is accumulated in the few hands, they can control people and enslave them individually and collectively in the fields of politics, economy, social, ethical, media and so forth. Having prudent provisions Islam eradicates the accumulation of wealth and accordingly distributes it among the largest number of people as possible. Thus, Islam commands inheritance distribution and encourages making the will for parents, relatives as well as for charity and welfare institutions. Also, Islam motivates to feed the poor and needy and care for orphans, disabled, widows and widowers. Apart from the obligation of zakah, Islam also encourages to make waqf for charity, needy relatives, and for public and private facilities such as schools, libraries, hospitals, mosques, and others.